2010
DOI: 10.1016/s1413-8670(10)70054-4
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of sepsis in a Brazilian teaching hospital

Abstract: The data from our study revealed a high incidence of sepsis among hospitalized patients. Moreover, sepsis patients had a high rate of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
1
9
1
4
Order By: Relevance
“…In agreement with a recent epidemiological study in a Brazilian hospital in the state of Paraná, we found that the main medical cause for ICU admission was sepsis (35% against 40% in Kauss et al 29 recent study), and the mortality rates at ICU plus follow-up were 46% in our study compared to 42% in Kauss et al 29 Our study revealed no association between -308G > A TNF-α genotypes and adverse outcomes (sepsis, septic shock, higher organ dysfunction or mortality) from critical illness. Our results demonstrated that the -308A rare allele frequency was 15%, confirming the trend documented in Danish (22%), 24 English (20%), 23 French (18%), 17 and Spanish subjects (9%).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with a recent epidemiological study in a Brazilian hospital in the state of Paraná, we found that the main medical cause for ICU admission was sepsis (35% against 40% in Kauss et al 29 recent study), and the mortality rates at ICU plus follow-up were 46% in our study compared to 42% in Kauss et al 29 Our study revealed no association between -308G > A TNF-α genotypes and adverse outcomes (sepsis, septic shock, higher organ dysfunction or mortality) from critical illness. Our results demonstrated that the -308A rare allele frequency was 15%, confirming the trend documented in Danish (22%), 24 English (20%), 23 French (18%), 17 and Spanish subjects (9%).…”
Section: Discussionsupporting
confidence: 93%
“…Es la principal causa de mortalidad en pacientes críticamente enfermos no coronarios con una tasa entre 19,6 y 59% 2,3 . La mortalidad es atribuida a la falla de diferentes órga-nos, entre los cuales el sistema cardiovascular es objeto de interés 4 .…”
Section: Introductionunclassified
“…These findings have been already described and indicate the importance of studying sepsis diagnoses and their effect on nursing activities in the ICU. [22] The increased workload during the first week most likely reflects the application of the early care measures recommended by the international guidelines for patients with sepsis and the measures taken to prevent and treat the organ dysfunctions that commonly occur among these patients at the onset of treatment. [3] Recent study found that excessive nursing workload was the most important risk factor for acquiring nosocomial infection.…”
Section: Discussionmentioning
confidence: 99%